Editorial: twenty minutes of moderate‐to‐vigorous physical activity a day keeps the NAFLD away—authors' reply. Issue 1 (14th December 2021) - Tsunoda, Kenji; Kitano, Naruki; Kai, Yuko; Jindo, Takashi; Uchida, Ken; Arao, Takashi
LINKED CONTENT: This article is linked to Tsunoda et al papers. To view these articles, visit https://doi.org/10.1111/apt.16631 and https://doi.org/10.1111/apt.16662